ENHANCING FARMER’S WELL BEING THROUGH THE AGRICULTURE LAND PROVISIONS IN WEST NUSA TENGGARA - Baiq Rindang Aprildahani; Chrisna Trie Hadi Permana; Surya Tri Esthi Wira Hutama (GeoEco, 2021)
While carrying out its essential duties to provide adequate foods for people, the agriculture sector is facing sustainability issues. The study presents a case study of West Nusa Tenggara (NTB), whereby an increase of urban expansion activities has begun to create a centrifugal force to the province that is popularly called as the granary of Indonesia. Urban settlements slowly leapfrogged to the outskirts and reduced the size of prime agricultural lands. Moreover, existing planning policies were unable to control the situation and many farmers leave their jobs because the setback of farmers wellbeing. The size of agricultural land is highly influential towards farmer motivation to stay engaged in the farming sector. Applying qualitative methods, this study examined the minimum area of agriculture land (focusing on paddy field) to promote farmer’s well-being following three steps of the analytical framework: total agricultural production estimation, the average well-being estimation, and the prediction of minimum land provision for the average well-being. After all, one of the key important findings reveals that the average of minimum agricultural land to ensure famers wellbeing for the whole NTB Province is 0.74 Ha.